2009
DOI: 10.1590/s1677-04202009000300008
|View full text |Cite
|
Sign up to set email alerts
|

L-myo-InositoL-1- phosphate synthase from bryophytes: purification and characterization of the enzyme from Lunularia cruciata (L.) Dum

Abstract: L-myo-inositol-1-phosphate synthase (MIPS; EC: 5.5.1.4) catalyzes the conversion of D-glucose-6-phosphate to 1L-myo-inositol-1-phosphate, the rate limiting step in the biosynthesis of all inositol containing compounds. Myo-inositol and its derivatives are implicated in membrane biogenesis, cell signaling, salinity stress tolerance and a number of other metabolic reactions in different organisms. This enzyme has been reported from a number of bacteria, fungi, plants and animals. In the present study some bryoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Our results are however in complete agreement with the reports published earlier (Chettri et al 2006a;2006b;Basak et al 2012). The plastidial MIPS exhibited a temperature optima of 35 °C, which is also in complete congruence with majority of the published reports sans a few where a lower temperature maxima for MIPS has been recorded (Chettri et al 2005;2006a;2009). This may be attributed to the variation in the habitat of the experimental sample(s).…”
Section: Mips Activitysupporting
confidence: 93%
“…Our results are however in complete agreement with the reports published earlier (Chettri et al 2006a;2006b;Basak et al 2012). The plastidial MIPS exhibited a temperature optima of 35 °C, which is also in complete congruence with majority of the published reports sans a few where a lower temperature maxima for MIPS has been recorded (Chettri et al 2005;2006a;2009). This may be attributed to the variation in the habitat of the experimental sample(s).…”
Section: Mips Activitysupporting
confidence: 93%
“…The partially purified of D. cordata FBPase was incubated in presence of the variable concentration of individual metal ions mentioned, to the usual assay components and keeping one control set without adding any such cation. Results of such experiments have been shown in table 6. Among the monovalent cations tested, K + , Na + and NH4 + slightly enhanced FBPase activity at least upto 10mM, on the contrary Li + was a very effective inhibitor of this enzyme.…”
Section: Effect Of Monovalent and Divalent Cationsmentioning
confidence: 97%
“…Using increasing concentration of Drymaria cordata enzyme protein from from 0-400µg, Fructose-1,6bisphosphatase assay was carried out under optimal conditions. It has been revealed that the Drymaria cordata FBPase activity has increased linearly with the increase of protein concentration up to 300µg (Table 5), whereas the activity of Ginkgo biloba enzyme) increased upto a concentration of 400µg (Yonzone et al, 2015) while a related enzyme, inositol synthase from Lunularia cruciata showed similar value i.e., increased upto a concentration of 300µg (Chhetri et al, 2009).…”
Section: Progress Of Fbpase Reaction With Respect To Protein Concentrmentioning
confidence: 99%